ANALISIS SIYASAH TANFIDZIYYAH DALAM IMPLEMENTASI REGULASI PENGENDALIAN LIMBAH BAHAN BERBAHAYA DAN BERACUN - Maudi Debita Rusanah; Iskandar Syukur; Ahmad Fauzi Furqon (CV Widina Media Utama, 2026)
This study aims to analyze the controversy surrounding alleged pollution from Hazardous and Toxic Substances (B3) resulting from the mining activities of PT Abadi Ogan Cemerlang (AOC) in Ogan Komering Ulu Regency. The analysis was conducted from the perspectives of Siyasah Tanfidziyyah and positive environmental law using a juridical-empirical method. Data were collected through field interviews with affected communities and activists from the NGO Pemuda Hijau Sumsel. The results of the study indicate a significant gap between formal-administrative aspects and the empirical reality on the ground. Although an inspection by the Environmental Agency (DLH) in October 2025 indicated normal parameters, residents confirmed that pollution from mining sludge sediment in the Lempaung and Wal Rivers continues. Overflow from the Sludge Retention Pond (KPL) during the rainy season triggers a health crisis in the form of skin disease outbreaks and mass fish deaths. Viewed through the lens of Siyasah Tanfidziyyah and Maqashid asy-Syariah, this situation violates the principles of Hifdzun Nafs (preservation of life) and Hifdzul Maal (preservation of property). PT AOC’s current relief assistance scheme is merely curative and temporary, failing to address the root causes of the problem in a preventive and solution-oriented manner. Based on the fiqh principle of Adh-Dhararu Yuzalu, local executive authorities are required to maximize their oversight functions and enforce strict sanctions to uphold the public interest. The novelty of this research lies in the integration of positive environmental law and a critical reconstruction of Siyasah Tanfidziyyah to develop a sustainable model for mitigating ecological conflicts at the site level. ABSTRAKPenelitian ini bertujuan menganalisis polemik dugaan pencemaran limbah Bahan Berbahaya dan Beracun (B3) akibat aktivitas penambangan PT Abadi Ogan Cemerlang (AOC) di Kabupaten Ogan Komering Ulu. Analisis dilakukan melalui perspektif Siyasah Tanfidziyyah dan hukum lingkungan positif menggunakan metode yuridis-empiris. Data dihimpun melalui wawancara lapangan bersama masyarakat terdampak serta aktivis LSM Pemuda Hijau Sumsel. Hasil penelitian menunjukkan adanya celah (gap) signifikan antara aspek formal-administratif dengan realitas empiris di lapangan. Meskipun pemeriksaan Dinas Lingkungan Hidup (DLH) pada Oktober 2025 menunjukkan parameter normal, warga mengonfirmasi bahwa pencemaran sedimen lumpur sisa tambang di Sungai Lempaung dan Sungai Wal tetap berlanjut. Luapan Kolam Penampungan Lumpur (KPL) saat musim hujan memicu krisis kesehatan berupa wabah penyakit kulit dan kematian massal ikan. Ditinjau dari Siyasah Tanfidziyyah dan Maqashid asy-Syariah, kondisi ini mencederai prinsip Hifdzun Nafs (menjaga jiwa) dan Hifdzul Maal (menjaga harta). Skema dispensasi bantuan dari PT AOC baru bersifat kuratif-sementara dan belum menyentuh akar permasalahan yang preventif-solutif. Berdasarkan kaidah fikih Adh-Dhararu Yuzalu, pemegang otoritas eksekutif daerah dituntut memaksimalkan fungsi pengawasan dan ketegasan sanksi demi menegakkan kemaslahatan publik. Kebaruan penelitian ini terletak pada integrasi hukum lingkungan positif dan rekonstruksi kritis Siyasah Tanfidziyyah untuk menghasilkan model mitigasi konflik ekologis di tingkat tapak secara berkelanjutan.